In Silico Analysis of Saponin Isolates from Mesocarp of Cucumber (Cucumic sativus L.) and Purple Eggplant (Solanum melongena L.) as Pancreatic Lipase Inhibitor. Issue 1 (May 2020) - Wijaya, Mely; Subandi,
Abstract: Currently orlistat has been widely used as anti-obesity drug, because of its activity as a pancreatic lipase inhibitor. Two saponin isolates, from cucumber mesocarp and purple eggplant, also proved to be active as pancreatic lipase inhibitors in vitro. Based on spectrophotometric analysis, the two saponin isolates are thought to be Silphioside F and Cesdiurins I-III. The purpose of this study is to confirm the ability of the two compounds as pancreatic lipase inhibitor through in silico analysis, relative to orlistat. This study uses Python Molecular Viewer (PyMol), Python Prescription (PyRx) 0.8, and Discovery Studio software. As a ligand, 3D structure of Silphioside F and Cesdiurins I-III have been used. The orlistat as a comparative ligand molecule have also been used. 3D structure of porsine pancreatic lipase has been used as receptor molecule. The result of the analysis shown that the binding site of pancreatic lipase is relatively same as orlistat of Cesdiurins I-III molecule, but different for the Silphioside F molecule. The data indicated that in inhibiting pancreatic lipase, the two isolate compounds used different mechanism. However, against pancreatic lipase, both molecules have greater binding affinities each, compared to orlistat, which were -9.7 kcal/mol for Silhphioside F and -9.5 kcal/mol for Cesdiurins I-III, and orlistat only -7.6 kcal/mol. The latest data were in line with the in vitro analysis, that both isolates have greater inhibition power than orlistat.